Analysis of Economic Value Added (EVA) and Market Value Added (MVA) as Tools for Measuring Company Financial Performance (A Study on PT United Tractors, Tbk for the 2021-2023 Period) - Nadia Safa Shabira; Lia Julaeha (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to assess the financial performance of PT United Tractors, Tbk for the 2021–2023 period using the Economic Value Added (EVA) and Market Value Added (MVA) methods. This research is descriptive in nature and employs a quantitative approach. The analysis techniques used in this study include documentation and literature review. The study uses secondary data in the form of the company’s annual financial statements, particularly the statement of financial position and income statement, obtained from the official website of PT United Tractors, Tbk and the Indonesia Stock Exchange. Based on the EVA and MVA analysis of PT United Tractors, Tbk for the 2021–2023 period, the company demonstrates positive performance despite fluctuations. EVA increased from 2021 to 2022, reflecting capital efficiency, although it declined in 2023 due to a decrease in NOPAT. MVA also rose from 2021 to 2022, indicating wealth creation, but declined in 2023 in line with a drop in the share price.